THE EFFECTS OF KURDISH LEARNERS' CHARACTERISTICS ON THEIR ENGLISH LANGUAGE LEARNING - Ivan Murad (European Scientific Journal, ESJ, 2015)
This paper is conducted at the University of Zakho, department of English language studies in (2013-2014). It investigates Kurdish learners' characteristics and their effects on the process of their second language learning. The data of the current study was collected throughout a methodological triangulation utilizing a questionnaire which consisted of 13 questions and it was given to a 100 students from different level in English department. Also a number of students were interviewed (2 students from each level) in order to obtain as reliable and authentic data as possible; the interview questions were 10. This research paper has been conducted to provide a detailed presentation of the learners’ characteristics and investigates their effects on the process of second language learning. It is revealed that the majority of the students are affected by some main characteristics such as anxiety, personality and motivation. And also the results and findings revealed that the majority of the students have some characteristics that affect their level in the process of second language learning in both ways negative and positive.